Insider Trading, News Releases, and Ownership Concentration - FIDRMUC, JANA P.; GOERGEN, MARC; RENNEBOOG, LUC (Journal of Finance, 2006)
ABSTRACT This paper investigates the market's reaction to U.K. insider transactions and analyzes whether the reaction depends on the firm's ownership. We present three major findings. First, differences in regulation between the U.K. and United States, in particular the speedier reporting of trades in the U.K., may explain the observed larger abnormal returns in the U.K. Second, ownership by directors and outside shareholders has an impact on the abnormal returns. Third, it is important to adjust for news released before directors' trades. In particular, trades preceded by news on mergers and acquisitions and CEO replacements contain significantly less information.